Analisis Faktor-Faktor yang Mempengaruhi Volatilitas Harga Saham pada Perusahaan Non Keuangan di Bursa Efek Indonesia - Meily Juliani (Global Financial Accounting Journal, 2021)
The purpose of this research is to analyze the factors that affect stock price volatility on non-financial companies listed in Indonesia Stock Exchange. The dependent variable studied is the stock price volatility, while independent variables were examined dividend yield, dividend payout ratio, firm size, asset growth, leverage, earning per share, and earning volatility. The secondary data obtained from the annual financial statements and reports of the company’s daily closing share price on the Indonesia Stock Exchange. This study used a sample of 130 companies listed in Indonesia Stock Exchange in the period of 2011-2015. The method used in analyzing the data is multiple regression model. The research data that has been collected will be tested using Eviews 8.0. The result of this study indicate that asset growth has a positive and significant impact on stock price volatility. While leverage and earning per share showed a negative and significant impact on stock price volatility. The result of this study also showed that the dividend yield, dividend payout ratio, and firm size did not have any significant impact on stock price volatility.